PEMANFAATAN SOSIAL MEDIA TIKTOK DALAM MENGEDUKASI SISWA KURANG MAMPU UNTUK MENDAFTAR KIP KULIAH 2025 - Syamsurijal; Akbar, Azaz (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Tuition fees pose a challenge for many underprivileged students to continue their education at higher education institutions. The Smart Indonesia Program is a solution introduced by the government to accommodate underprivileged students who wish to pursue education in both public and private universities. Although the Smart Indonesia Program has been in operation for several years, the socialization regarding how to register for KIP college has not been optimal, resulting in many students not receiving comprehensive information for KIP college registration. Reflecting on the existence of misdirected KIP College funds, one effective solution that can be used to educate students on how to register for college is to create educational content and technical guidelines for KIP college registration via TikTok. TikTok is a social media platform utilized by most senior high school students, and it is hoped that education regarding KIP college through TikTok can maximize the reach of KIP college information. The educational activities for KIP college registration are conducted in the form of creating content regarding the registration procedures for KIP College. The education method for KIP college is divided into live streaming sessions and the production of educational content through video series, as well as sharing videos that outline how to register for KIP college created by the Ministry of Education and Culture. The research results show that many students still do not fully understand how to register for KIP college, as evidenced by numerous inquiries regarding both the registration procedures and the necessary documentation. The education for KIP college registration through TikTok also received positive feedback from students, reflected in the views of the educational registration videos reaching hundreds of thousands, even millions, along with a significant number of shares, saves, comments, and likes. In conclusion, the role of TikTok social media as a platform for sharing KIP college registration information is very effective and efficient.